Correlation between coordinated water content and proton conductivity in Ca-BTC-based metal-organic frameworks - Mallick, Arijit; Kundu, Tanay; Banerjee, Rahul (Chemical Communications, 2012)
Proton conductivity of five Ca-based MOFs which depends on the amount of water molecules coordinated to the Ca-centres has been reported. These MOFs show high temperature proton conductivity due to the strong hydrogen bonding between the lattice and coordinated water molecules.

Crystalline metal-organic frameworks (MOFs): synthesis, structure and function - Dey, Chandan; Kundu, Tanay; Biswal, Bishnu P.; Mallick, Arijit; Banerjee, Rahul (Acta Crystallographica Section B-Structural Science, 2014)
Metal-organic frameworks (MOFs) are a class of hybrid network supramolecular solid materials comprised of organized organic linkers and metal cations. They can display enormously high surface areas with tunable pore size and functionality, and can be used as hosts for a range of guest molecules. Since their discovery, MOFs have experienced widespread exploration for their applications in gas storage, drug delivery and sensing. This article covers general and modern synthetic strategies to prepare MOFs, and discusses their structural diversity and properties with respect to application perspectives.

Catecholase and phenoxazinone synthase activities of a ferromagnetically coupled tetranuclear Cu(II) complex - Mitra, Merry; Kundu, Tanay; Kaur, Gurpreet; Sharma, Gyaneswar; Choudhury, Angshuman Roy; Singh, Yogesh; Ghosh, Rajarshi (RSC Advances, 2016)
A crystallographically characterized tetranuclear Cu(II) complex [Cu-4(II)(L)(4)] (1) [H2L = N-(2-hydroxyethyl)-3-methoxysalicylaldimine] is found to show overall ferromagnetic exchange coupling. Complex (1) mimics the catalytic activity of the plant enzyme catechol oxidase by oxidising 3,5-di-tert-butylcatechol to its corresponding quinone in methanol and dichloromethane medium in the presence of aerial oxygen. The reaction follows Michaelis-Menten enzymatic reaction kinetics with turnover numbers (K-cat) 6.99 x 10(3) and 1.85 x 10(3) h(-1) in methanol and dichloromethane, respectively. 1 is also phenoxazinone synthase active in methanol medium with a turnover number of 1.21 x 10(5) h(-1).